Pengaruh Person Organization Fit Dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior di PT Kereta Api Indonesia (PERSERO) - Endri Haryati; Agus Purbo Widodo (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Person-organization fit is defined as the alignment between the values of the organization and the values of the individual. Person-organization fit refers to the compatibility of an employee with their organization. Person-organization fit has been defined in various ways, including value congruence, goal congruence, and the match between employee needs. Organizational commitment is defined as an employee's attachment to a particular organization, its goals, and their desire to maintain membership within the organization. Citizenship Behavior (OCB) is a term used for employees who provide added value to their assigned tasks as well as additional benefits to the company. PT Kereta Api Indonesia (Persero), hereinafter abbreviated as KAI or "the Company," is a State-Owned Enterprise that provides, manages, and oversees rail transportation services in Indonesia. Based on the results of analysis and discussion, this study uses Path Diagrams and Hypothesis Testing with the Partial Least Squares (PLS) method using the SmartPLS 3.0 program. The Path Diagram is used to visualize the influence pathways between variables in the research. The validity test results show that the indicators for each variable have a loading factor greater than 0.7, confirming the validity of these indicators in measuring Person-organization Fit (P-O fit), organizational commitment, and organizational citizenship behavior. Additionally, convergent validity was evaluated using the Average Variance Extracted (AVE), where all research variables had AVE values above 0.5. The reliability of the indicators was also confirmed to be high, with Cronbach's Alpha and Composite Reliability values for each variable exceeding 0.6 and 0.7, respectively. Structural Model Evaluation shows that the variable organizational citizenship behavior is explained by 14.9% through the variables Person-organization Fit (P-O fit) and organizational commitment. The hypothesis test results indicate that Person-organization Fit (P-O fit) and organizational commitment significantly influence organizational citizenship behavior among employees of PT. Kereta Api Indonesia (PERSERO), with a p-value of 0.011 < 0.05. Based on these conclusions, it is recommended to include additional independent variables in future research to broaden the understanding of the Organizational Citizenship Behavior variable, which in this study was only explained by 26.6%. Thus, this study provides significant contributions to understanding the relationship between Person-organization Fit (P-O fit), organizational commitment, and organizational citizenship behavior among employees of PT. Kereta Api Indonesia (PERSERO), while offering suggestions for further development in future research.